Evaluation and Implementation of EMI/EMC Compliance for a Proposed Power Electronics-Based Converter Topology for Electric Vehicles - Tekin, Hakan; Vatansever, Seyit; Ertekin, Davut (Elektronika ir Elektrotechnika, 2024)
The demand for high-gain, efficient, and cost-effective power converters with simple control mechanisms to connect electric vehicle batteries to the grid is increasing. This study introduces a switched capacitor-based power boost converter circuit to meet these needs. The minimal number of power switches in the circuit simplifies control operations and improves practical applicability. The proposed converter boosts the battery pack voltage by a factor of 5 and 11 for duty ratios of 0.5 and 0.8, respectively, which is significant compared to conventional boost converters. However, designing an electromagnetic interference (EMI) filter is crucial when a power converter board requires the application of a wide range of switching frequencies to enhance electromagnetic compatibility (EMC) immunity. Therefore, as the next step, the EMI/EMC filter design stages were discussed for the proposed converter. For this purpose, 15 printed circuit board (PCB) design rules were checked using the Altium Designer EMI Design Rule Checker, and board EMI/EMC compatibility was analysed. The resonance between the power and ground layers in the PCB was assessed using the plane resonance analyser. The results of simulation and laboratory tests are presented, which confirms the theoretical studies. On the basis of the software results, the points on the electronic board most susceptible to visual interferences have been identified. To minimise these EMI/EMC errors, it is suggested to add electronic components, such as capacitors, at these points according to mathematical and software findings.